Electroconvulsive therapy use for refractory status epilepticus in an implantable vagus nerve stimulation patient: A case report - Katzell, Lauren; Beydler, Emily M.; Holbert, Richard; Rodriguez-Roman, Laura; Carr, Brent R. (Frontiers in Psychiatry, 2023)
Introduction Status epilepticus (SE) has a mortality rate of 20-50%, with acute symptomatic SE having a higher risk compared to chronic SE. Electroconvulsive therapy (ECT) has been utilized for the treatment of refractory SE with a success rate estimate of 57.9%.1–3 There are no known reported cases of concomitant use of VNS and ECT for the treatment of super refractory SE (SRSE) available in the literature. Case Description We present a 44-year-old female with a history of developmental delay, epilepsy, an implantable VNS for six years, and traumatic brain injury with subsequent hygroma who presented with progressive aphasia, declining mental status, and daily generalized seizures lasting up to 20 minutes. Seizures had increased from her baseline of one seizure per day controlled with topiramate 200 mg three times daily and lamotrigine 400 mg twice daily. She was diagnosed with SRSE after being intubated and placed on eight anti-epileptic drugs (AEDs) that failed to abort SE. ECT was attempted to terminate SE. Due to a prior right craniotomy with subsequent right hygroma, eight treatments of ECT were performed over three sessions using a right anterior, left temporal and subsequently a bitemporal electrode placement. The VNS remained active throughout treatment. Various ECT dosing parameters were attempted, varying pulse width and frequency. Although ECT induced mild transient EEG changes following ECT stimulations, it was unable to terminate SE. Discussion This case describes various treatment strategies, constraints, and device limitations when using ECT for the treatment of SE. With wide variability in efficacy rates of ECT in the treatment of SE in the literature, successful and unsuccessful cases offer information on optimizing ECT total charge dose and parameters that yielded success. This case demonstrates an instance of ECT inefficacy in the treatment of SRSE. Here, we discuss the rationale behind the various ECT settings that were selected, and constraints arising from the antiepileptic burden, VNS, and intrinsic limitations of the ECT device itself.